An Overview of the Skin Microbiome, the Potential for Pathogen Shift, and Dysbiosis in Common Skin Pathologies - Anita Smith; Roberta Dumbrava; Noor-Ul-Huda Ghori; Rachael Foster; James Campbell; Andrew Duthie; Gerard Hoyne; Marius Rademaker; Asha C. Bowen (Microorganisms)
Recent interest in the diverse ecosystem of bacteria, fungi, parasites, and viruses that make up the skin microbiome has led to several studies investigating the microbiome in healthy skin and in a variety of dermatological conditions. An imbalance of the normal skin flora can cause some skin diseases, and current culture techniques are often unable to detect a microorganism to further our understanding of the clinical–microbiological correlates of disease and dysbiosis. Atopic dermatitis and rosacea are presentations that GPs often manage that may have an infective or microbiological component and can be challenging to treat. We aim to discuss the implications of the skin microbiome including the impact of dysbiosis on conditions such as these. We will also discuss some clinical pearls for initial and future directions of the management of conditions such as atopic dermatitis, rosacea, and hidradenitis suppurativa. Further research using culture-independent techniques is needed for conditions involving microbial dysbiosis to advance our knowledge of skin disease pathophysiology and guide future management.